The Influence of Knowledge, Image, and Service of Islamic Banks on Adoption of Sustainable Financial Practices: Evidence from University Students in Indonesia - Alqodri, Fajrunas (Yayasan Darussalam Patalassang, 2025)
This study aims to analyze the influence of Islamic financial literacy, bank image, and perceived service quality on students’ decisions to adopt Islamic banking in Indonesia. Using a quantitative survey approach, data were collected from students through structured questionnaires and statistically analyzed to examine the relationships among variables. The findings reveal that a high level of Islamic financial literacy, a positive bank image, and favorable perceptions of service quality collectively enhance students’ intentions to use Islamic banking services. These results indicate that improving literacy, credibility, and service quality can foster greater trust and participation of young generations in Islamic finance. The study underscores the importance of education-based strategies, brand reputation, and digital service excellence in strengthening the role of Islamic banks in promoting sustainable and inclusive financial development.